Terahertz radar cross‐section characterisation using laser feedback interferometry with quantum cascade laser. Issue 22 (13th October 2015) - Lui, H.S.; Taimre, T.; Bertling, K.; Lim, Y.L.; Dean, P.; Khanna, S.P.; Lachab, M.; Valavanis, A.; Indjin, D.; Linfield, E.H.; Davies, A.G.; Rakić, A.D.
Abstract : Radar cross‐section (RCS) measurements of complex, large objects are usually performed on scale models so that the measurement is carried out in a well‐controlled environment. The feasibility of RCS measurement using a terahertz (THz) quantum cascade laser (QCL) via laser feedback interferometry is explored. Numerical simulations show that the RCS information embedded in the nonlinear interferometric signals obtained from simple targets can be retrieved through numerical fitting of the well‐known excess phase equation. The method is validated experimentally using a THz QCL and the results are well matched with those obtained from numerical simulations.